Development and evaluation of a lead oxide flexible skin dosimeter with a silicon passive layer. (1st February 2022) - Yang, S.W.; Han, M.J.; Park, S.K.; Choi, M.Y.; Moon, Y.M.; Bae, S.I.; Park, S.H.; Kang, Y.R.; Rah, J.E.; Chung, J.B.; Kim, J.Y.
Abstract: Normal tissues are also exposed during radiation therapy. In particular, the skin is highly sensitive to radiation. Therefore, care should be taken regarding excessive exposure, and the dose irradiated to the skin should be measured accurately. In this study, a skin dosimeter that can be attached to the human body was manufactured using a silicone binder, and a new type of passive layer using silicon was applied. In addition, the manufactured dosimeter was evaluated to establish whether it could be used with a skin dosimeter. The observation of the surface of the dosimeter through SEM analysis showed that cracks did not occur on the surface of the silicon passive layer PbO dosimeter when it was bending. The bending silicon passive layer PbO dosimeter's relative standard deviation was 1.45%, meeting the evaluation criteria of 1.5%. The linearity evaluation showed that the R 2 of the bending silicon passive layer PbO dosimeter was 0.9996, satisfying the evaluation criterion R 2 of 0.9990. The PDD measurements showed that the D_max points matched. As the silicon passive layer PbO dosimeters showed no cracks when bending, high signal stability, and accuracy in reproducibility, linearity, and PDD measurement results, it could be suitable for application as skin dosimeters.